Optimalisasi Program Pemerintah dalam Meningkatkan Kesejahteraan Ekonomi Pemerlu Pelayanan Kesejahteraan Sosial (PPKS) di Rusunawa Solokan Jeruk - Damayanti, Sri; Ramdhani, Nurul Rahma; Alia, Nayla Rahma; Aziz, Rushi Mu’min (Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses the optimization of improving economic welfare for Social Welfare Service Recipients (PPKS) in Rusunawa Solokan Jeruk, West Java. The Participatory Rural Appraisal (PRA) method was used in this study which aims to identify the potential, needs, and active involvement of PPKS in the empowerment program. The results show that the program has succeeded in increasing independence, with several families starting small businesses and children returning to school. However, challenges in the form of social stigma and difficulties in adaptation still hinder the effectiveness of the program. Routine monitoring and evaluation are essential to ensure the sustainability and effectiveness of the intervention. This study recommends further studies on PPKS economic empowerment to strengthen a more inclusive and sustainable approach in social welfare policy.